IDENTIFIKASI GEN SELENOMETIL TRANSFERASE (smt) PADA ISOLAT Geobacillus sp. 20K YANG RESISTEN TERHADAP SELENIUM - Triana, Evi; Nurhidayat, Novik; Yulinery, Titin; Kasim, Ernawati; Dewi, Ratih M (BERITA BIOLOGI, 2010)
The trace element Selenium is toxic at high concentration.Most of organisms living in selenium rich environment are selenium resistant.One of the resistance mechanisms is methylation,in which selenium is methylated and transformed to non-toxic selenium compound.The methylation is catalyzed by seleno methyltransferase (SMT) coded by smt gene. The gene are expressed by selenium tolerant plants. However, there was no available report yet on such specific gene in the bacterial genome. This study was carried out to determine smt homologous gene on selected selenium accumulator bacteria, Geobacillus sp. 20k, The smt gene of was determined by amplifying target DNA and analyses its sequences through homology search (BLAST). The result showed that the DNA and its protein part of thermophilic enzyme involved selenium metabolisms.